Mediation of a GDSL Esterase/Lipase in Carotenoid Esterification in Tritordeum Suggests a Common Mechanism of Carotenoid Esterification in Triticeae Species - Requena-Ramírez, María Dolores; Atienza, Sergio G.; Hornero-Méndez, Dámaso; Rodríguez-Suárez, Cristina (Frontiers in Plant Science, 2020)
Carotenoids are essential in human diet, so that the development of programs towards carotenoid enhancement has been promoted in several crops. Tritordeum, the amphiploid derived from the cross between Hordeum chilense Roem. et Schulz. and durum wheat, has a remarkable carotenoid content in the endosperm. Besides, a high proportion of these carotenoids are esterified with fatty acids. The identification of the gene(s) responsible for xanthophyll esterification would be useful for breeding as esterified carotenoids present an increased ability to accumulate within plant cells and have a higher stability during post-harvest storage. In this work, we analysed five genes identified as candidates for lutein esterification in H. chilense genome. All of them were expressed during grain development in tritordeum but only HORCH7HG021460 was highly upregulated. Sequence analysis of HORCH7HG021460 revealed a Glycine to Cysteine change in the zero-ester accession H290 of H. chilense compared to the esterifying genotypes. An allele-specific marker was designed for the SNP detection in the H. chilense diversity panel. From the 93 accessions, only H290 showed the mutant genotype and the zero-esters phenotype. Furthermore, HORCH7HG021460 is the orthologue of XAT-7D which encodes a xanthophyll acyltransferase enzyme (XAT) responsible of carotenoid esterification in wheat. Thus, HORCH7HG021460 (XAT-7Hch) is a strong candidate for lutein esterification in tritordeum suggesting a common mechanism of carotenoid esterification in cereals. The transference of XAT-7Hch to wheat may be useful for lutein esters enhancement in biofortification programs.